On Construction of Ecological Classroom Teaching Mode - Lu, Jie; Zhang, Zhiqiang (International Journal of English Literature and Social Sciences (IJELS), 2019)
Ecological classroom teaching mode is a teaching situation that is people-oriented, student-centered and focuses on students’ personality development.The basic characteristics of ecological classroom are as follows: authenticity, nature and harmony; life, growth and wisdom;Integrity, openness and improvement.This paper discusses the construction of ecological classroom teaching model from three aspects: teacher-student relationship, student-student relationship and classroom teaching environment.It points out that ecological classroom is the paradise of healthy growth of students and the paradise of sustainable development of teachers.It shows that the construction of ecological classroom teaching mode is beneficial to the overall improvement of classroom teaching efficiency and the overall improvement of students' life quality.